Faktor yang mempengaruhi likuiditas perusahaan tekstil dan garmen di Bursa Efek Indonesia (BEI) periode 2019 – 2021 - Sopakuwa, Benardus Rogger; Gomulia, Budiana; Faisal, Achmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The textile and garment industry is an industrial sector that plays an important role in driving the economy in Indonesia. According to the Minister of Industry of the Republic of Indonesia, amid the Covid-19 pandemic, there were liquidity problems in the textile and garment industry in Indonesia. This study aims to determine the factors that influence the liquidity of textile and garment companies on the IDX for the period 2019-2021. There are several independent variables tested, among others, company size, opportunity to grow, and working capital turnover. The population used in this study were all 21 textile and garment companies on the IDX. While the sample was taken using purposive sampling technique, in order to obtain 15 companies with a total sample of 164. Data analysis was carried out using multiple linear regression method. The results of the study show that the size of the company has a positive and significant effect on liquidity.